Relationship between cognitive need and learning styles in students of UNMSM - Delgado Vásquez, Ana (2000)
It is analized the relationship between need for cognition and Kolb's learning styles theory, considering Freshmen students at a public university (Universidad Nacional Mayor de San Marcos, UNMSM). Participants were 489 students, chosen randomly from 19 Academic Schools or "Facultades". The results showed that students have high levels of need for cognition and that male students have the highest score. It was found that the learning style Divergent is the most frequent, while the style assimilator was the least frequent. The styles Convergent and Divergent are the most common among male and female students, respectively. Also, it was found that the measures of learning styles and need for cognition showed significative relationship. Active experimentation showed no signification relationship with need for cognition.